Pengembangan E-Modul Ajar Bermuatan Artificial Intelligence untuk Meningkatkan Keterampilan Berpikir Kritis dan Keterampilan Komunikasi Siswa - Azizah S. Pairunan; Nurjannah; Haeruddin; Unggul Wahyono; Marungkil Pasaribu (Jurnal Penelitian Pendidikan IPA, 2025)
The increasingly rapid development of digital technology requires the world of education to adapt to various innovations, one of which is the use of artificial intelligence (AI) in learning. However, in reality, many schools still use conventional, less interactive teaching materials, thus not optimally improving 21st-century skills, particularly critical thinking and communication skills. This research aims to produce a suitable and effective artificial intelligence-based e-learning module for improving students' critical thinking and communication skills. The research employed a mixed methods approach with an embedded experimental model design, consisting of several stages: introduction, design, development, and interpretation. The research subjects were 60 students of class X of SMA Negeri 5 Sigi. The research instruments included expert validation sheets, cognitive assessment tests (functioning as pretest and posttest), observation sheets on student communication skills and observation sheets on student activities during the learning process, and interview guidelines after the learning process. This study concludes that the development of e-learning modules containing artificial intelligence is effective and feasible for use in improving students' critical thinking and communication skills.